Modulation of TonEBP activity by SUMO modification in response to hypertonicity - Kim, Jeong-Ah; Kwon, Mi Jin; Lee-Kwon, Whaseon; Choi, Soo Youn; Sanada, Satoru; Kwon, Hyug Moo (Frontiers in Physiology, 2014)
TonEBP is a DNA binding transcriptional enhancer that enables cellular adaptation to hypertonic stress by promoting expression of specific genes. TonEBP expression is very high in the renal medulla because local hypertonicity stimulates its expression. Given the high level of expression, it is not well understood how TonEBP activity is modulated. Here we report that TonEBP is post-translationally modified by SUMO, i.e., sumoylated, in the renal medulla but not in other isotonic organs. The sumoylation is reproduced in cultured cells when switched to hypertonicity. Analyses of site-directed TonEBP mutants reveal that K556 and K603 are independently sumoylated in response to hypertonicity. DNA binding is required for the sumoylation. Functional analyses of non-sumoylated mutants and SUMO-conjugated constructs show that sumoylation inhibits TonEBP in a dose-dependent manner but independent of the site of SUMO conjugation. Sumoylation inhibits transactivation without affecting nuclear translocation or DNA binding. These data suggest that sumoylation modulates the activity of TonEBP in the hypertonic renal medulla to prevent excessive action of TonEBP.